2020
DOI: 10.1007/s00167-020-06266-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparable clinical and radiological outcomes between anatomical and high femoral tunnels in posterior cruciate ligament reconstruction

Abstract: Purpose To compare clinical and radiological outcomes and failure rates between anatomical and high femoral tunnels in remnant-preserving single-bundle posterior cruciate ligament (PCL) reconstruction. Methods 63 patients who underwent remnant-preserving single-bundle PCL reconstruction between 2011 and 2018 with a minimum 2-year follow-up were retrospectively reviewed. Patients were divided into two groups according to the femoral tunnel position: group A (33 patients with anatomical femoral tunnel) and group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…No additional studies were found upon manually checking the reference lists of the selected articles. Thus, 13 studies were included in the analysis [1, 5, 10, 11, 13–17, 19, 32–34]. Of the 13 included articles, one was level II [32], five were level III [1, 11, 17, 33, 34], and seven were level IV [5, 10, 13–16, 19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No additional studies were found upon manually checking the reference lists of the selected articles. Thus, 13 studies were included in the analysis [1, 5, 10, 11, 13–17, 19, 32–34]. Of the 13 included articles, one was level II [32], five were level III [1, 11, 17, 33, 34], and seven were level IV [5, 10, 13–16, 19].…”
Section: Resultsmentioning
confidence: 99%
“…The data regarding the surgical technique followed in each of the examined studies are displayed in Table 2. The type of graft used in the various studies was as follows: six studies reported the use of Achilles allograft [1,11,13,[32][33][34], five studies autologous hamstrings [1,5,10,16,17], and three studies tibialis allografts (anterior or posterior) [14,15,19]. The femoral graft-fixation construct was performed in 10 studies with a screw [1,5,10,11,13,16,17,[32][33][34], and with the RigidFix System in three studies [14,15,17], while the Endobutton System was employed in one study only [19].…”
Section: Surgical Protocolmentioning
confidence: 99%
“…Graft failure after PCL reconstruction was defined as follows: the need for additional surgery (revision PCL reconstruction, knee arthroplasty, high tibial osteotomy, etc), a complete tear of the PCL graft on MRI, or grade 3 instability on stress radiography (SSD >10 mm). 28 The patients were divided into 2 groups according to failure or nonfailure, and subgroup analysis was performed for the medial PTS and lateral PTS subgroups. The 10-year graft survival rates were calculated and compared between the small and large PTS subgroups of the medial PTS and lateral PTS groups.…”
Section: Methodsmentioning
confidence: 99%
“…All surgical procedures were performed using the same method by a single experienced surgeon. [26][27][28][29]31 Arthroscopic SB PCL reconstruction was performed with Achilles tendon allografts 10 mm in diameter. The tibial orifice of the PCL tunnel was targeted at a point distal and lateral to the original site of the tibial attachment of the PCL.…”
Section: Surgical Technique and Postoperative Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation